Psychometrics of the moral distress scale in Iranian mental health nurses - Raziyeh Ghafouri; Sara Lotfi-Bajestani; Malihe Nasiri; Kayoko Ohnishi; Foroozan Atashzadeh-Shoorideh (BMC, 2021)
Abstract Background One of the challenges that nurses often face in ethical decision-making situations is moral distress. Moral distress is caused by the conflict between professional and individual values in decision-making situations. Despite its importance, there is no reliable scale in Persian to measure it. Therefore, this study was conducted to validate the moral distress scale in mental health nurses in Iranian culture and Persian language. Methods This study was conducted in two parts: Translation and cross-cultural adaptation and psychometric analysis. The translation and cross-cultural adaptation process was conducted based on the Polit approach. Next, face validity (qualitative), content validity (quantitative and qualitative), and construct validity were examined. This part of the study was a cross-sectional study. In this step, a demographic questionnaire and the Moral Distress Scale were sent to 500 nurses working in selected educational and medical centers in Iran via online questionnaires. Then, the construct validity of the "Moral Distress Scale" was confirmed by confirmatory factor analysis and the reliability of the instrument was examined by studying the internal consistency with Cronbach's alpha and the internal correlation of the AIC. Results The confirmatory factor analysis showed an acceptable ratio of the expressions in 15 items in three factors: Acquiescence to patients' rights violations (6 items), Unethical conduct by caregivers (5 items), and low staffing (4 items) in the scale. The internal consistency of the instrument with Cronbach's alpha was higher than 7.0. Conclusion The Persian version of moral distress with 15 items of the three factors had validity and reliability. According to the present findings, this scale can be used to study moral distress among nurses working in psychiatric wards. Moral distress leads to burnout, increases risks to patient safety and reduces quality of care. Nurses need to be able to assess and manage moral distress. Therefore, considering the side effects, it is necessary to have a reliable and valid scale that can be studied. Considering that culture has an impact on nurses' moral distress, it is suggested that this instrument be studied in and tested in other languages and cultures.